Zika virus inhibits eIF2α-dependent stress granule assembly. - Raquel Amorim; Abdelkrim Temzi; Bryan D Griffin; Andrew J Mouland (PLoS Neglected Tropical Diseases, 2017)
Zika virus (ZIKV), a member of the Flaviviridae family, is the most recent emerging arbovirus with pandemic potential. During infection, viruses trigger the host cell stress response, leading to changes in RNA translation and the assembly of large aggregates of stalled translation preinitiation complexes, termed stress granules (SGs). Several reports demonstrate that flaviviruses modulate the assembly of stress granules (SG). As an emerging pathogen, little is known however about how ZIKV modulates the host cell stress response. In this work, we investigate how ZIKV modulates SG assembly. We demonstrate that ZIKV negatively impacts SG assembly under oxidative stress conditions induced by sodium arsenite (Ars), a treatment that leads to the phosphorylation of eIF2α. By contrast, no measurable difference in SG assembly was observed between mock and ZIKV-infected cells treated with sodium selenite (Se) or Pateamine A (PatA), compounds that trigger eIF2α-independent SG assembly. Interestingly, ZIKV infection markedly impaired the phosphorylation of eIF2α triggered in Ars-treated infected cells, and the abrogation of SG assembly in ZIKV-infected cells is, at least in part, dependent on eIF2α dephosphorylation. These data demonstrate that ZIKV elicits mechanisms to counteract host anti-viral stress responses to promote a cellular environment propitious for viral replication.